2003
DOI: 10.1021/ja036596i
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linked Bis-hemoglobins:  Connections and Oxygen Binding

Abstract: Covalently linked pairs of cross-linked hemoglobin tetramers ("bis-tetramers", shown schematically as 6-8) were prepared by reacting hemoglobin A with tetrakis acyl phosphate esters (3-5). The effects of the link between tetramers are observed in the oxygen-binding properties of the bis-tetramers: they bind oxygen cooperatively but with Hill coefficients (n(50)) lower than that of the native protein and with a high average affinity. The bis-tetramers with longer connections between tetramers show a higher n(50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…Reagent 1, with a central sulfone, gave the highest yield of a ∼128 kDa material (Table 1). Globin chain analysis (32) through C4 reverse-phase HPLC showed that only one component derived from native hemoglobin had been modified (Figure 2 (20) and counterparts isophthalyl phosphastes (23,24) that produced cross-linked hemoglobin bis-tetramers.…”
Section: Resultsmentioning
confidence: 99%
“…Reagent 1, with a central sulfone, gave the highest yield of a ∼128 kDa material (Table 1). Globin chain analysis (32) through C4 reverse-phase HPLC showed that only one component derived from native hemoglobin had been modified (Figure 2 (20) and counterparts isophthalyl phosphastes (23,24) that produced cross-linked hemoglobin bis-tetramers.…”
Section: Resultsmentioning
confidence: 99%
“…The bridge-span portion of the three reagents connected to Hb is shown as 6, 7, and 8 in Scheme 2. 35 The P 50 s (pO 2 at which the HBOC is halfsaturated with O 2 ) of the bis-tetramers synthesized from reagents were 5.0 AE 0.1, 4.2 AE 0.1, and 4.3 AE 0.1 mm Hg respectively, whereas the bridge-span distance was 14. Cross-linking reagents 3 and 4 (Scheme 3) possessed flexible but saturated hydrocarbon chains and yielded cross-linked Hb tetramers (E and F) without a second protein moiety.…”
Section: Site-specific Hboc Designmentioning
confidence: 98%
“…In one of their first studies, Kluger's group cross-linked pairs of Hb tetramers with N,N 0 -5,5 0 -bis[bis-(3,5-dibromosalicyl)-isophathalyl]-terephthalamide (shown as 1 in Scheme 1), a tetrafunctional intra-/intermolecularly capable crosslinking reagent. 33,35 Reagent 1 consisted of two bridgespanned pairs of reaction sites, which react with the lysyl amino groups (b-82) of hHb to yield the Hb bis-tetramer (shown as 2 in Scheme 1) product with reduced oxygen binding cooperativity (n ¼ 1.3). 35 Gourianov and Kluger expanded on the previous study and then reported on the synthesis of relatively longer bridge-spanned cross-linking reagents with increased rigidity and coupled in pairs.…”
Section: Site-specific Hboc Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Dendrimers represent one such class of molecules. Kluger and his colleagues (Hu and Kluger 2008;Gourianov and Kluger 2003) have developed a variety of intramolecularly crosslinked Hbs, particularly targeted to the bb-cleft of the molecule. A new approach for increasing the molecular size of Hb, i.e.…”
Section: Conjugation Of Hb To a Globular Synthetic Polymermentioning
confidence: 99%